The Effect of Water Hardness on Surfactant Deposition after Washing and Subsequent Skin Irritation in Atopic Dermatitis Patients and Healthy Control Subjects - Danby, Simon G.; Brown, Kirsty; Wigley, Andrew M.; Chittock, John; Pyae, Phyoe K.; Flohr, Carsten; Cork, Michael J. (Journal of investigative dermatology, 2018)
Living in a hard water area is associated with an increased risk of atopic dermatitis (AD). Greater skin barrier impairment after exposure to surfactants in wash products, combined with the high calcium levels of hard water and/or high chlorine levels, is a compelling mechanism for this increase. The purpose of this study was to investigate this mechanism in individuals with and without a predisposition to skin barrier impairment. We recruited 80 participants: healthy control subjects and AD patients with and without FLG mutations. The skin of each participant was washed with sodium lauryl sulfate in water of varying hardness levels and chlorine concentrations, rinsed, and covered with chambers to determine the effects of surfactant residues. Sites washed with hard water had significantly increased sodium lauryl sulfate deposits. These deposits increased transepidermal water loss and caused irritation, particularly in AD patients carrying FLG mutations. A clear effect of chlorine was not observed. Water softening by ion-exchange mitigated the negative effects of hard water. Barrier impairment resulting from the interaction between hard water and surfactants is a contributory factor to the development of AD. Installation of a water softener in early life may be able to prevent AD development. An intervention study is required to test this hypothesis.